Geobiomes of Burdur-Golhisar Basin in the Lakes Subregion of the Mediterranean Region in Turkey - Atalay, Ibrahim; Altunbas, Sevda; Siler, Muzaffer (Istanbul Univ Press, Istanbul Univ Rectorate, 2019)
Geobiomes can be referred the effects of geologic parent materials and topographic particularities on some ecological properties of soil formation, plant growth and productivity, land capability classification, land-use of the given area. In order the importance of the geobiomes Burdur-Golhisar Basin containing different parent materials and geomorphic units is taken as study area in the northwest part of the Mediterranean Region of Turkey. Serpentine-Peridotite Biome. Serpentine forms a distinct habitat in terms of plant growth and soil formation. Deep weathered serpentine produces fertile soil due to almost all plant nutriments released, while unweathered and low weathered serpentine forms a poor habitat on which poor stand forest and bare land is common. Moreover, cracks on the serpentine supports the growth of individual trees. Marl Biome is found on the marl deposit. The amount of clay, sand-silt, and inclination of layer of marl deposit affect directly the soil formation and plant growth. Clay-rich marl deposit often prevents the vertical root structure of trees and soil formation takes long time more than a few millions. Good stand forests are found on the soft and inclined layered marl deposits. Severe erosion continues the steep slopes of marl deposit. Karst Biome occurring on the limestone creates a special environment depending on crackiness, amount of clay content and the inclination of limestone layers in the karstic land. Generally, red Mediterranean soil has developed along the cracks and among the layers on the sloping area. Other important property of karstic land is to allow forming a good natural regeneration of forest trees. Conglomerate karst biome occurs on the conglomerate and sandstone containing mostly limestone gravels and sands, and calcareous cement. The weathering of the calcareous cement material especially along the soft zones and cracks causes disintegration of conglomerates and sandstones as gravels and sands. Here sandy loam soil is widespread. Halobiome is common on the regressed Lake Burdur shore on which sparse halophytes grow. Hydrobiomes cover in places where ground water level is high and narrow swampland. Here hydrophytic vegetation grows on the hydromorphic soil and hydromorphic alluvial soil. Psammo-litho biomes are found on the dejection fans and cones, and lithosols on the sloping area.
1st Istanbul International Geography Congress -- JUN 20-22, 2019 -- Istanbul, TURKEY
Keywords: Geobiomes; Soil formation; Plant Growth; Geomorphology; Burdur-Golhisar Basin